Liderazgo del maestro : requisito esencial para la excelencia docente (2017)
The present research aims to identify the soft skills and behaviors that characterize teacher leadership, for which it develops three phases. The first phase has two components: a) a systematic review of the literature and b) a documentary analysis. The second phase is advanced from the methodology of phenomenology, conducting semi-structured interviews with teachers who have achieved important performances in their work and who have been awarded for excellence in their role; In support of phenomenology, the organizational theory of critical incidents is used. The third phase comprises the analysis and triangulation of the information obtained in the different sources. The research does not find a clear identification in the international literature of the skills and behaviors necessary for the exercise of teaching leadership. In addition, the skills required for the exercise of teaching leadership are: Innovation, initiative and creativity, teamwork, support and guidance to students, teaching with the example and reflective attitude...